The Opportunities for and Limitations on a Finnish Female Artist in Lapland before the Second World War - Hautala-Hirvioja, Tuija (Journal of Finnish Studies, 2022)
Since the 1840s in Finland, there have been equal possibilities for men and women to study art. This article examines the possibilities and limitations that women had to take into account to study fine arts. To understand the situation in Finland during the 1920s and 1930s, I use as a case the life and art of Maija Kellokumpu (1892–1935). She was an exceptional individual who lived in Lapland, the northernmost region of Finland. Her home village, Kelloselkä, is located about thirty-three miles north of the Arctic Circle and northeast near the present border between Finland and Russia. Maija Kellokumpu was the daughter of a religious, agricultural family from the small and traditional village. I study her life and her art from a microhistorical viewpoint; her biography is at the center, but it expands with contextualization: the salient frames of reference are northern culture and religion, the Finnish world of art, and the status of women. Finland was for one hundred years a part of the Russian Empire and became independent in December 1917. Soon, in the spring of 1918, the Finnish Civil War broke out and lasted four months. The young, independent country began to develop during the next few decades, but the development stopped in November 1939 when the Winter War started. As part of my study, I focus on the limitations and suspicions to which women's careers were subjected—some of which are based in the realms of religion, economics, and education, while some are art-world based in terms of the tension and distance between the art-center and peripheries, as well as the lack of money and patrons.